(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2018)
The paper tries to answer the following tricky question: what is the role of the law – and namely of bio-law – in regulating science and technology? In societies where a common ethics cannot be found, is it possible for the law to put limits to the practices offered by the scientific progress? As the paper points in the conclusion, the reference to the Constitutional principles can provide a pivotal key to face the hard challenges of this field.